Process method for regulating and controlling micro-nano structure of porous cell wall of wood and dyeing at low temperature

By delignification and bleaching the wood, the micro-nano structure of its cell wall is regulated, and the dyeing is used with reactive dyes under low temperature conditions, the problems of poor permeability of wood staining and low dyeing rate are solved, uniform and efficient dyeing effect is achieved, and dyeing stability and color fastness are improved.

CN119589776APending Publication Date: 2025-03-11NANJING FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411783300.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing wood staining technology is difficult to achieve uniform and efficient dyeing while ensuring the integrity of the microstructure of wood, and there are problems such as low dyeing rate, insufficient color fastness and high energy consumption.

Method used

By delignification and bleaching the wood, the micro-nano structure of its cell wall is regulated, the permeability and reaction binding active sites are increased, and the dye is stained with Procion MX type reactive dye and NaCl under low temperature conditions. Through vacuum impregnation, sonication and water bath color fixation technology, the deep binding of dyes and wood fibers is promoted.

Benefits of technology

It significantly improves the dyeing stability and color fastness of wood, enhances the permeability and binding force of dyes, reduces dyeing temperature and time, reduces energy consumption, and increases the added value of low-value wood.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119589776A_ABST
    Figure CN119589776A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wood dyeing, in particular to a process method for regulating and controlling a wood porous cell wall micro-nano structure and dyeing at low temperature. The method comprises the following steps that wood is subjected to delignification treatment in a mixed solution of NaOH and Na2SO3, and delignified wood is obtained; the delignified wood is placed in an H2O2 solution to be subjected to bleaching treatment, and bleached modified wood is obtained; and the bleached and modified wood is placed in a dyeing solution for dyeing treatment, and then color fixing treatment is conducted. According to the method, wood is subjected to delignification / bleaching to regulate and control a cell wall structure, the permeability is improved, micro-nano fluid channels are increased, and reaction binding active sites are increased; and the chemical reaction between the wood fiber and the dye is promoted to generate a fiber-dye covalent bond, so that the problems of color fading and the like of the wood under light, damp and hot conditions are prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wood dyeing, and in particular to a process method for regulating the micro-nano structure of porous cell walls of wood and dyeing at low temperature. Background Art

[0002] Wood is an important renewable resource material. It is widely used in furniture, decoration, sports equipment and construction due to its low cost, natural texture and psychologically comfortable visual characteristics. Wood dyeing is a method to eliminate color changes and overcome the monotony of color on the basis of maintaining the natural properties of wood. It can also imitate the color of precious wood species, increase the added value of low-value wood, and enhance visual characteristics and decorative performance.

[0003] Wood is a material with a multi-level pore structure of macroscopic pores, mesoscopic pores and microscopic pores. There are pore structures of different shapes in the wood cell wall, which provide necessary channels for the transmission of substances. The diffusion and penetration process of liquid inside wood mainly occurs in the interconnected cell cavities (duct cavities), intercellular spaces and small pores on the cell wall pit membrane, as well as the micro-nano pores between microfibrils and between basic fibrils on the cell wall.

[0004] The essence of wood dyeing is the penetration and fixation process of dye solution inside the wood. The dye molecules in the dye solution first penetrate into the wood through porous fluid channels such as wood cell cavities and intercellular spaces, and then adsorb, settle and fix on the fiber surface to achieve dyeing. However, the complex structure of the porous cell wall of wood makes it difficult for traditional dyeing methods to accurately penetrate and evenly color, especially during the dyeing process, which can easily lead to structural damage or uneven dyeing. The cell wall of wood is modified to be porous to increase the number of its pore structure or expand its pore structure. It not only provides channels for the transmission of dyes and increases the accessibility of dye molecules on cellulose molecules, but also provides more active sites for the fixation and reaction of dyes, thereby enhancing the stability and dyeing effect of dyed wood. In summary, the development of a new dyeing process that can achieve uniform and efficient dyeing while ensuring the integrity of the wood microstructure has become the focus of research.

[0005] At present, in the research of many scholars, the factors affecting wood dyeing mainly include dyeing temperature, dyeing time and dye concentration. The dyeing temperature is roughly between 60℃ and 95℃. The higher the dyeing temperature, the higher the kinetic energy the dye molecules can obtain, thereby overcoming the resistance to diffusion into the wood. Therefore, as the temperature rises, the dye uptake rate tends to rise. However, the increase in temperature will cause the dye and wood to decompose, and a large amount of energy will be consumed. In addition, the dyeing time in many studies is roughly between 4h and 9h. The extension of dyeing time is conducive to the full impregnation of the dye into the wood and the maximum attachment to the wood fiber. However, too long a time will not only cause the dye to hydrolyze, but also a large amount of it will accumulate at the entrance of the porous channel, causing blockage and reducing the penetration of dye molecules. In the process of dyeing wood, energy consumption and material waste are undoubtedly a major challenge. In summary, it is meaningful to study the method of low-temperature rapid dyeing to reduce energy consumption. Summary of the invention

[0006] Based on the above content, the present invention provides a process method for regulating the micro-nano structure of porous cell walls of wood and low-temperature dyeing.

[0007] To achieve the above object, the present invention provides the following solutions:

[0008] One of the technical solutions of the present invention is a process for regulating the micro-nano structure of porous cell walls of wood and low-temperature dyeing, comprising the following steps:

[0009] The wood was mixed with NaOH and Na 2 SO 3 delignification treatment is performed in a mixed solution to obtain delignified wood;

[0010] The delignified wood is placed in H 2 O 2 Bleaching treatment is performed in the solution to obtain bleached modified wood;

[0011] placing the bleached and modified wood in a dyeing solution for dyeing, and then performing a color fixing treatment;

[0012] The dyeing solution includes a Procion MX type reactive dye and NaCl.

[0013] A second technical solution of the present invention is a dyed wood prepared according to the above method.

[0014] A third technical solution of the present invention is the application of the dyed wood in the fields of furniture, decoration, sports equipment or construction.

[0015] The present invention discloses the following technical effects:

[0016] In order to solve the problems of poor permeability and low dye uptake of wood dyeing, the present invention performs delignification / bleaching on wood to regulate the cell wall structure, improve the permeability and increase the micro-nano fluid channels, as well as increase the reaction binding active sites; promote chemical reaction between wood fiber and dye to generate fiber-dye covalent bonds, thereby preventing the wood from fading under light, humidity and heat conditions.

[0017] The dyed wood prepared by the method of the present invention has improved stability after dyeing, and the production process is easy to control, and the problems of low dye uptake and insufficient color fastness during dyeing are solved. The light fastness is significantly enhanced, and the color difference after ultraviolet light irradiation is small. The process of vacuum impregnation, ultrasonic treatment, and then water bathing can allow the dye to penetrate into the interior of the wood to the maximum extent, and the dye molecules aggregated after vacuum impregnation are dispersed through ultrasonic treatment, so that the dye and the wood can be more combined. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 These are actual pictures of dyed wood (dyed poplar, dyed pine) in Examples 1 and 2; wherein, a is a solution of Procion MX yellow, orange, blue dye and Reactive blue dye at a concentration of 0.1wt%; b is a picture of natural poplar, hydrogen peroxide-treated poplar and delignified poplar dyed with the four dyes in a; c is a picture of natural pine, hydrogen peroxide-treated pine and delignified pine dyed with these four dyes.

[0020] Figure 2 It is a diagram of the internal dyeing of the dyed wood in Examples 1 and 2.

[0021] Figure 3 These are the transverse, radial and tangential scanning electron microscope images of the poplar log in Example 1; wherein a is a physical image of a portion of natural poplar wood cut away, b is an electron microscope image of the radial section of the log, c is an electron microscope image of the tangential section of the log, and d is an electron microscope image of the cross section of the log.

[0022] Figure 4 These are the transverse, radial and tangential scanning electron microscope images of the delignified poplar wood in Example 1; wherein a is a physical image of the delignified poplar wood, b is an electron microscope image of a radial section, c is an electron microscope image of a tangential section, and d is an electron microscope image of a cross section.

[0023] Figure 5 The contents of cellulose, hemicellulose and lignin in the poplar logs and delignified poplar in Example 1.

[0024] Figure 6 : The mercury adsorption pore size distribution of the poplar log and delignified poplar in Example 1.

[0025] Figure 7 These are radial, tangential and transverse scanning electron microscope images of the dyed poplar wood in Example 1; wherein a is a real image of the delignified dyed poplar wood, b is a radial scanning electron microscope image, and c is a tangential scanning electron microscope image.

[0026] Figure 8 It is the permeability diagram of poplar and pine in Examples 1 and 2; wherein a is the path length of the solution penetrating the sample, b is the permeability of poplar logs (natural poplar) and delignified poplar, and c is the permeability of pine logs (natural pine) and delignified pine.

[0027] Fig. 9 These are large-format sample images of poplar wood in Example 1; wherein, a is a large-size sample of Procion MX orange dyed poplar wood in Example 1, b is a large-size sample of Procion MX blue dyed poplar wood in Example 1, and c is a picture showing the effect of curling the dyed poplar wood in b.

[0028] Fig.10 This is a diagram of the water loss resistance of poplar wood in different directions in Example 1; wherein a is a physical image of water loss treatment in different directions, and b is the loss rate.

[0029] Fig.11 These are images of delignified and dyed poplar wood in Example 1 under extreme conditions such as low temperature, high temperature, humidity, acidity and alkalinity.

[0030] Fig.12 The color difference of the delignified and dyed poplar wood in Example 1 under extreme conditions such as low temperature, high temperature, humidity, acidity and alkalinity.

[0031] Fig.13 This is the color fastness to light of the delignified dyed poplar wood in Example 1.

[0032] Fig.14 The dimensional stability of the delignified dyed poplar wood in Example 1.

[0033] Fig.15 This is a test of the friction performance of poplar wood in different directions in Example 1.

[0034] Fig.16 These are transverse and longitudinal scanning electron microscope images of the pine log in Example 2; wherein a is an electron microscope image of the cross section of the pine log, b is an electron microscope image of the corner of the cell wall of the pine log, and c is a longitudinal electron microscope image.

[0035] Fig.17 These are the transverse and longitudinal scanning electron microscope images of the delignified pine wood in Example 2; wherein, a is the transverse image of the delignified pine wood, b is the electron microscope image at the corner of the cell wall, and c is the longitudinal scanning electron microscope image.

[0036] Fig.18 These are the transverse and longitudinal scanning electron microscope images of the dyed pine wood in Example 2; wherein, a is the transverse direction of the dyed pine wood, b is the electron microscope image at the corner of the cell wall, and c is the longitudinal scanning electron microscope image.

[0037] Fig.19 This is a graph showing the water loss resistance of pine wood of different thicknesses in Example 2; wherein a is an image of water loss treatment of pine wood of different thicknesses, and b is the loss rate.

[0038] Fig. 20 These are images of pine wood contaminated and stained by different pollutants in Example 2; wherein a is the image of the pollutant, and b is the image of the contaminated and stained pine wood. DETAILED DESCRIPTION

[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0040] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0044] The first aspect of the present invention provides a process for regulating the micro-nano structure of porous cell walls of wood and low-temperature dyeing, comprising the following steps:

[0045] The wood was mixed with NaOH and Na 2 SO 3 delignification treatment is performed in a mixed solution to obtain delignified wood;

[0046] The delignified wood is placed in H 2 O 2 Bleaching treatment is performed in the solution to obtain bleached modified wood;

[0047] The bleached and modified wood is placed in a dyeing solution for dyeing treatment, and then a color fixing treatment is performed.

[0048] The dyeing solution includes a Procion MX type reactive dye and NaCl.

[0049] In the present invention, the micro-nano structure of the wood cell wall is regulated by delignification treatment.

[0050] In the present invention, the purpose of bleaching is to remove the chromophore and auxochrome groups that affect the dyeing effect.

[0051] The present invention retains structural integrity, improves permeability, increases micro-nano fluid channels, and reaction binding sites by delignifying / bleaching the wood. The present invention imparts colors that low-value wood does not have by itself through dyeing, thereby increasing the added value of low-value wood and reducing waste of resources.

[0052] In a preferred embodiment of the present invention, the concentration of NaOH in the mixed solution is 0.5 to 2.5 mol L -1 , Na 2 SO 3 The concentration is 0.1~0.4mol L -1 According to the specific practical application requirements, the concentration, temperature and time are adjusted to obtain the best delignification effect. In some embodiments of the present invention, when the thickness of the wood is 1 mm, 2.5 mol L -1 NaOH and 0.4 mol L -1 Na 2 SO 3 , the processing time is 6h.

[0053] In the present invention, NaOH and Na 2SO 3 Too high a concentration will cause other components in the wood (such as cellulose) to be excessively degraded or dissolved, thus destroying the wood structure. The mixed solution under this condition can maintain the basic structure of the wood and remove lignin.

[0054] In a preferred embodiment of the present invention, the temperature of the delignification treatment is 80-100° C. and the time is 3-6 hours.

[0055] In a preferred embodiment of the present invention, the delignification treatment further comprises a step of rinsing with water after completion.

[0056] In a preferred embodiment of the present invention, the H 2 O 2 The concentration of the solution was 10 wt%.

[0057] In a preferred embodiment of the present invention, the bleaching treatment is specifically bleaching until the delignified wood becomes white.

[0058] In some specific embodiments of the present invention, the bleaching time is about 1 to 3 hours to whiten the delignified wood.

[0059] In a preferred embodiment of the present invention, the bleaching treatment further comprises the steps of washing with water and drying.

[0060] In a preferred embodiment of the present invention, the concentration of the Procion MX type reactive dye in the dyeing solution is 0.1 wt% to 1 wt%; the concentration of NaCl in the dyeing solution is 10 to 50 g L -1 .

[0061] In a preferred embodiment of the present invention, the dyeing treatment is specifically as follows: first dyeing at a negative pressure of -0.08 to -0.1 MPa for 20 to 30 minutes, then ultrasonicating at a power of 800 to 1000 W for 20 to 30 minutes, and then keeping warm at 30 to 60° C. in a water bath for 2 to 3 hours.

[0062] In a preferred embodiment of the present invention, the color fixing treatment is specifically to add Na 2 CO 3 Treat in a water bath at 30-60°C for 30 min; 2 CO 3 The concentration in the dye solution is 10-20 g L -1 .

[0063] A second aspect of the present invention provides a dyed wood prepared according to the above method.

[0064] A third aspect of the present invention provides a use of the dyed wood in the fields of furniture, decoration, sports equipment or construction.

[0065] The present invention adjusts the porous structure of wood and increases permeability by chemical means, constructs micro-nano pore structure on the cell wall, including pore size, pore distribution and pore microstructure, and removes chromophores and auxochromes that affect the dyeing effect. Then, under the condition of 30°C to 60°C, active dyes, dye accelerators and color fixatives are selected as dyeing liquid, and the dye molecules and wood fibers are formed into COC covalent bonds by controlling the uniform penetration of the dye in the wood cell wall, and the dyed wood is obtained after 2 to 3 hours of treatment. The obtained dyed wood maintains color stability under extreme conditions such as low temperature, high temperature, humidity, acidity and alkalinity, and has good ultraviolet weather resistance. In addition, the dyed wood material also has good dimensional stability and wear resistance.

[0066] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0067] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0068] Example 1

[0069] (1) 1 mm thick natural poplar wood (Populus 1) was cut into 3 cm × 3 cm pieces and placed in a 2.5 mol L -1 NaOH and 0.4 mol L -1 Na 2 SO 3 The wood was subjected to a mixed solution (the solvent was water) of 1,4-dimethylformamide and 1,4-dimethylformamide, and delignified in a water bath at 80° C. for 6 h. After the delignification treatment, the wood was rinsed with deionized water for 3 times under vacuum to remove residual chemicals, thereby obtaining delignified wood.

[0070] (2) The delignified wood was placed in a 10 wt% H 2 O 2 The sample was bleached in a solution (the solvent was water) until it turned white, and then washed with deionized water for 3 times and dried at 60° C. for 32 h to obtain bleached modified poplar wood (ie, delignified poplar wood).

[0071] (3) The poplar wood bleached and modified in (2) was placed in a humidified environment with a dye concentration of 0.1 wt% and a NaCl concentration of 30 g L -1The dye solution (the six dyes in the dye solution are Procion MX fuchsia, yellow, turquoise, blue, red and orange) was vacuum dyed at a negative pressure of -0.08 to -0.1 MPa. After 20 minutes of treatment, it was transferred to an ultrasonic (1000w) cleaning device for 20 minutes of ultrasonication, and finally placed in a 40°C water bath for reaction for 140 minutes. After that, 20g L -1 Na 2 CO 3 The sample was treated in a water bath (45°C) for 30 minutes and dried at 60°C for 48 hours to obtain dyed poplar wood.

[0072] The natural poplar, delignified wood and dyed poplar in Example 1 were tested as follows:

[0073] The sample after dyeing in Example 1 is as follows Figure 1 As shown in b (Control in the figure represents undyed poplar wood chips; wherein a is a solution of Procion MX yellow, orange, blue type dye and Reactive blue dye with a concentration of 0.1wt% from left to right; b is natural poplar wood (Nature wood, which is different from Example 1 only in that steps (1) and (2) are omitted) and hydrogen peroxide treated poplar wood (H 2 O 2 , that is, the only difference from Example 1 is that step (1)) and delignified poplar wood (NaOH / Na 2 SO 3 / H 2 O 2 , i.e., the dyed poplar wood obtained in Example 1); c is a picture of natural pine wood, hydrogen peroxide-treated pine wood, and delignified pine wood dyed with the four dyes in a). A small cut was made in the dyed sample, and it can be clearly observed that the inside of the wood is dyed (e.g., Figure 2 As shown in the figure, it can be clearly seen that the internal staining is basically consistent with the surface color, which indicates the uniform penetration of the dye inside the wood. And the hardwood (poplar) dyed with six different colors of PMX dyes (such as Procion MX fuchsia, yellow, turquoise, blue, red and orange) shows good internal and external color uniformity.

[0074] Scanning electron microscopy (SEM) was used to characterize natural poplar wood. Figure 3(Natural wood in the figure means natural wood, i.e. untreated natural poplar wood chips; the same below) It can be seen that natural poplar wood has a porous structure under the macroscopic view. The scanning electron microscope (SEM) image on the longitudinal section shows that there are significant pore structures on the vessel wall and cell wall. These pores provide important channels for the absorption and transportation of water, and also facilitate the penetration of dyes and other chemical reagents. However, these pores cannot meet the requirements of dyeing uniformity.

[0075] Depend on Figure 4 (Delignified wood in the figure refers to the delignified wood in Example 1; the same below) It can be seen that after chemical delignification, the honeycomb structure of poplar wood is retained, but most of the lignin is removed from the cell wall, especially in the intercellular layer where lignin is highly concentrated. Figure 5 It can be seen that delignification treatment increases the cellulose content of wood from 49.4% to 66.2%, and reduces the hemicellulose and lignin contents from 19.6% and 31% to 12.9% and 20.9%, respectively. Figure 6 Mercury adsorption tests show that the porosity of delignified wood chips increased significantly from 64.48% to 79.10% after chemical treatment, and the pore size range is about 1μm to 200μm. The changes in composition and pore size may have improved the structural integrity, permeability and dye absorption of the material. The substantial increase in porosity indicates an increase in permeability. The regulation of the cell wall micro-nanostructure greatly improves the dyeing effect of wood.

[0076] Figure 7 The SEM characterization of the dyed poplar prepared in Example 1. During the dyeing process, the dye particles penetrate deeply into the entire secondary wall of the cell wall, especially the pores and the inner cavity wall, through capillary action and penetration mechanism, and successfully gather in large quantities on the cell wall of the wood, and most of the particles even penetrate into the corners of the cell wall. It can be seen from Table 1 that the dye uptake of the wood is greatly improved after delignification treatment, among which the dye uptake of PMX orange dye is increased from 15.32% to 82.54%, and the improvement efficiency is as high as 5 times. At the same time, the dye uptake of other dyes (such as PMX fuchsia, PMX red and PMX blue) is also significantly improved.

[0077] Table 1 Dye uptake of natural wood (NW) and delignified wood (DW) after dyeing in Example 1.

[0078]

[0079] Permeability tests were conducted on natural wood and delignified wood, and the results were as follows: Figure 8 As shown ( Figure 8In the text, Poplar refers to poplar and Pinus refers to natural pine. Figure 8 It can be seen that for natural wood (poplar), the permeability of delignified wood increased by nearly 10 times.

[0080] Depend on Fig. 9 (In the figure, Wood fiber direction indicates the length direction of wood fiber) It can be seen that the dyed wood prepared in Example 1 has a large surface and a certain degree of curlability.

[0081] Fig.10 (In the figure a, from left to right, NW / D means natural poplar wood after dyeing, After leaching means NW / D after leaching, DW / D means delignified poplar wood after dyeing, After leaching means DW / D after leaching; Transversal means transverse direction, Longitudinal means longitudinal direction, L-NW / D means natural poplar wood dyed sample is used for leaching, L-DW / D means delignified poplar wood dyed sample is used for leaching) in Example 1, the water loss performance test of the untreated poplar wood and delignified poplar wood dyed samples was carried out, and the water loss rate of the wood after dyeing with Procion MXblue dye was less than 0.5%.

[0082] like Fig.11 (In the figure, Color Environmental Stability refers to the color stability performance under different environments, Acid solution refers to acidic solution, and Alkaline solution refers to alkaline solution) As shown, the color of dyed poplar wood has excellent stability under some extreme conditions. Specifically, Fig.12 As shown in the figure, after cold treatment at -50℃ for 6 hours, the color of delignified dyed poplar wood remained basically stable, and the ΔE value was 1.67±0.83, indicating that it has good color stability under extremely low temperature conditions. After high temperature treatment at 70℃ for 24 hours, ΔE was only 1.35±0.37. After soaking in hot water at 60℃ for 6 hours, ΔE increased to 5.7±0.75. In addition, in an acid-base environment, the dyed poplar wood was soaked in an acid solution with pH=1 and an alkaline solution with pH=13 for 6 hours, and the ΔE values ​​were 4.82±0.45 and 3.44±0.67, respectively.

[0083] like Fig.13As shown in the figure (in the figure, Delignified wood / dye means delignified wood dyeing, Aftersolarization means after xenon lamp sunlight treatment, PMX Red means Procion MX red dye, PMX Fuchsia means Procion MX fuchsia dye, PMX Turquoise means Procion MX turquoise dye, PMX Orange means Procion MX orange dye, the same below), in the xenon lamp exposure test, the test was stopped when the blue wool standard sample reached the second level of fading standard, and the light fastness grade of the treated samples was about 3, and the color difference ΔE was kept below 12, indicating that the dyed poplar wood has medium light fastness under xenon lamp irradiation.

[0084] Fig.14 (Delignifiedwood / dye in the figure means delignified wood dyeing) shows the dimensional changes of the dyed poplar wood prepared in Example 1 under different temperatures (20, 35, 50, 60°C). The dimensional changes at each temperature are kept within 2%, and no obvious expansion or contraction occurs, showing good dimensional stability.

[0085] Fig.15 The friction resistance experiment shows that after the dyed poplar wood prepared in Example 1 has undergone 1000 friction cycles on a 10 cm path and a sandpaper friction test, the surface color difference ΔE of the poplar wood remains at about 12, indicating that the prepared dyed poplar wood still maintains a certain color after friction.

[0086] Example 2

[0087] (1) Cut 1 mm thick natural pine wood into 3 cm × 3 cm pieces and place them in a 2.5 mol / L -1 NaOH and 0.4 mol L -1 Na 2 SO 3 The mixed solution (the solvent is water) was subjected to delignification treatment in a water bath at 80°C for 6 h, and the delignified sample was rinsed twice with deionized water under vacuum conditions to remove residual chemicals to obtain delignified wood;

[0088] (2) The delignified wood was placed in a 10 wt% H 2 O 2The pine wood was bleached in a solution (the solvent is water) until the sample turned white. After bleaching, it was washed twice with deionized water and dried at 60°C for 32 hours (24 to 48 hours) to obtain bleached modified pine wood (i.e., delignified pine wood).

[0089] (3) The poplar wood bleached and modified in (2) was placed in a humidified environment with a dye concentration of 0.1 wt% and a NaCl concentration of 30 g L -1 The dye solution (dyes: Procion MX fuchsia, yellow, turquoise, blue, red and orange) was vacuum dyed at a negative pressure of -0.08 to -0.1 MPa. After 20 minutes of dyeing, it was transferred to an ultrasonic cleaning device with 1000W ultrasound for 20 minutes, and finally placed in a 40°C water bath for reaction for 140 minutes. After that, 20g L -1 Na 2 CO 3 The sample was treated in a water bath (45°C) for 30 minutes and dried at 60°C for 48 hours to obtain dyed pine wood.

[0090] The natural pine wood, delignified wood and dyed pine wood in Example 2 were tested as follows:

[0091] Example 2 The dyed pine wood prepared Figure 1 As shown in c. The wood surface color is consistent with the dye color, such as Figure 2 As shown, a small cut is made in the dyed pine wood prepared in Example 2, and it can be clearly observed that the inside of the wood is dyed with color, and the color is relatively uniform, indicating that the dye penetrates the inside of the wood. And the coniferous wood (pine wood) dyed with six different colors of PMX dyes (such as Procion MX fuchsia, yellow, turquoise, blue, red and orange) shows good internal and external color uniformity.

[0092] The natural pine wood and delignified wood in Example 2 were characterized by scanning electron microscopy (SEM). Fig.16 As shown ( Fig.16 In the figure, Channel refers to the inner cavity, Pits refers to pits, and Tracheid refers to tracheid; the same below). The structure of natural pine wood is porous, and the void structure on the cell wall is limited. Fig.17 (In the figure, pore means pore) shows that after the pine wood in Example 2 is delignified, micro-nano pores are generated at the corners of the cell wall. Fig.18(In the figure, Dye particles represent dye particles, the same below) It can be seen that the dye molecules are obviously gathered in various parts of the cell wall, and even penetrate into the corners of the cell wall, as if embedded in the cell wall, which makes the connection between the cell walls tighter. In addition, the dye particles can enter the adjacent tracheids through the pores and are evenly distributed on the tracheid wall.

[0093] The permeability test was performed on the natural pine wood and delignified pine wood in Example 2. Figure 8 It can be seen that for pine wood, the permeability of delignified pine wood increased by nearly 3 times.

[0094] The natural pine wood and dyed wood in Example 2 were tested for water loss resistance (the samples were immersed in an aqueous solution, and the samples were taken out after 9 hours, and the dye content on the samples and the dye content in the filtrate were calculated to calculate the dye loss). Fig.19 It can be seen that the loss rate of pine wood of different thicknesses after dyeing with PMX blue dye is about 0.7%, which has good anti-loss performance.

[0095] Stain testing of stained pine with lubricating oil, coffee, soda, cooking oil and tea showed the following results: Fig. 20 As shown in the figure (in the figure, Lubricating (abbreviated as LO) means lubricating oil, Coffee (abbreviated as C) means coffee solution, Sodas (abbreviated as S) means soda water solution, Cooking oil (abbreviated as CO) means cooking oil, Tea (abbreviated as T) means tea, Before means before pollution treatment, Pollution means pollution treatment, and Water washing means washing with water). Fig. 20 It can be seen that oil-based pollutants will leave obvious stains on the surface of stained pine, while water-soluble pollutants will leave almost no traces.

[0096] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A process for regulating the micro-nanostructure of porous cell walls of wood and low-temperature dyeing, characterized in that: The following steps are involved: Delignifying the wood in a mixed solution of NaOH and Na2SO3 to obtain delignified wood; placing the delignified wood in a H2O2 solution for bleaching to obtain bleached modified wood; placing the bleached and modified wood in a dyeing solution for dyeing, and then performing a color fixing treatment; The dyeing solution includes a Procion MX type reactive dye and NaCl.

2. The process for regulating the micro-nanostructure of porous cell walls of wood and low-temperature dyeing according to claim 1, characterized in that: The concentration of NaOH in the mixed solution is 0.5-2.5 mol L -1 , Na2SO3 concentration is 0.1~0.4mol L - 1.

3. The process for regulating the micro-nanostructure of porous cell walls of wood and low-temperature dyeing according to claim 1, characterized in that: The temperature of the delignification treatment is 80-100° C. and the time is 3-6 hours.

4. The process for regulating the micro-nanostructure of porous cell walls of wood and low-temperature dyeing according to claim 1, characterized in that: The concentration of the H2O2 solution is 10 wt%.

5. The process for regulating the micro-nanostructure of porous cell walls of wood and low-temperature dyeing according to claim 1, characterized in that: The bleaching treatment is specifically bleaching until the delignified wood becomes white.

6. The process for regulating the micro-nanostructure of porous cell walls of wood and low-temperature dyeing according to claim 1, characterized in that: The concentration of the Procion MX type active dye in the dyeing solution is 0.1wt% to 1wt%; the concentration of NaCl in the dyeing solution is 10 to 50g L -1 .

7. The process for regulating the micro-nanostructure of porous cell walls of wood and low-temperature dyeing according to claim 1, characterized in that: The dyeing treatment is specifically as follows: first dyeing at a negative pressure of -0.08 to -0.1 MPa for 20 to 30 minutes, then ultrasonicating at a power of 800 to 1000 W for 20 to 30 minutes, and then keeping warm at 30 to 60° C. in a water bath for 2 to 3 hours.

8. The process for regulating the micro-nanostructure of porous cell walls of wood and low-temperature dyeing according to claim 1, characterized in that: The color fixation treatment is specifically to add Na2CO3 to the dyeing solution and treat it in a water bath at 30-60°C for 30 minutes; the concentration of Na2CO3 in the dyeing solution is 10-20 g L -1 .

9. The dyed wood prepared according to the method described in any one of claims 1 to 8.

10. Use of the dyed wood according to claim 9 in the fields of furniture, decoration, sports equipment or construction.